From Cash to Central Bank Digital Currency: Can Gen Z Adopt It? - Annes Nisrina Khoirunnisa; Moh Shadam Taqiyyuddin Azka; Nanik Shofiatin (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
This study aims to examine the intention of youth in Indonesia to adopt Central Bank Digital Currency (CBDC). A sample of 285 respondents was analyzed using SEM-PLS and in-depth interviews. The results of the study found that involvement facilitation, institutional trust, and technology trust had a significant effect on youth's intention to use CBDC. These findings emphasize the importance of building trust in technology and institutions, as well as increasing public confidence in the ability of central banks to launch and regulate CBDC systems. Empirical evidence also shows that facilitation and literacy provided by the authorities need to be a significant focus in addressing potential barriers to technology use among the public. Furthermore, there are maximum literacy facilities and consultation given can increase public confidence in CBDC provider authorities to continue to develop technology to the fullest.